Stability of Am(Ⅲ) Colloid and Its Adsorption Behavior on Bentonite Colloids - LIU Chen; FANG Sheng; XU Qiang-wei; XU Yu-wei; LONG Hao-qi; BAO Liang-jin; ZHOU Duo (He huaxue yu fangshe huaxue, 2022)
The formation of Am(Ⅲ) colloid and its adsorption behaviors on bentonite colloid were investigated in Beishan 03 groundwater. A series of influencing factors, such as, pH, CO2 concentration in gas atmosphere, ionic strength and temperature, on colloidal stability and adsorption behavior were explored using Zeta potential laser particle size analyzer, asymmetric flow field flow fractionation system(AF4) and batch experimental method. The results show that the formation and stability of Am(Ⅲ) are closely dependent on the chemical natures of aqueous solution. Increasing temperature or increasing ionic strength will reduce the stability of Am(Ⅲ) colloids, while the increase of carbon dioxide concentration and pH will be beneficial to the stability of Am(Ⅲ) colloid. In addition, with the increase of pH, the density of Am(Ⅲ)-bentonite colloid particles increases, while the Am(Ⅲ) adsorption rate first decreases and then increases; the increase of ionic strength is favor of Am(Ⅲ) adsorption, but the density of colloidal particles decreases; the increase of CO2 concentration in gas phase has a promoting effect on particle density and Am(Ⅲ) adsorption.